Crítica a la ciencia y a la tecnología en la obra de Juan León Mera (Crítica) - Rodrigo Mendizábal, Iván Fernando (2015)
This is the study of three stories of Juan León Mera wrote in the context of science fiction, apparently read and imitated by certain Ecuadorian authors, taking into account the literary publications appearing in Europe, particularly those of Jules Verne near the end nineteenth century. Mera, in a way, tries to use the style of science fiction but rather more humorously to make a critique of the political and social moment that he has to live. His concern that scientific and technological reason is penetrating Ecuadorian society, calling into question a certain cultural tradition of which Mera is the defender; it also has to do with the idea of progress that he does not completely share. The stories, published in literary magazines, are a clear expression of his stance against even what liberalism seems to proclaim: a new era and a change of mentality among the sciences. Although Mera admits that the sciences are important and should be cultivated, the political use of these, their mismanagement since there is no scientific school involved, threatens, indeed, any motivation to human progress he wanted to raise.